Zinc oxide, lidocaine, and lateral internal sphincterotomy for fissure-in-ano: a comparative study - Kaushal, Manish; Shukla, Arvind; P., Kovarthanan; Shivaprasad, Yogesh Heremat (International Surgery Journal, 2022)
Background: The aim of the study was to choose best method for management of fissure-in-ano. By comparing among zinc oxide pomade, lidocaine pomade and lateral internal sphincterotomy for treatment of anal fissure. Methods: 90 patients who were diagnosed with anal fissure between 2019 and 2021 at our MGM Medical College and M. Y. Hospital were undertaken for this prospective randomized trial. All cases randomized into three groups. Group 1 were the patients who applied 15% of zinc oxide pomade twice a day. Group 2 were the patients would apply 5% of lidocaine pomade twice a day. Group 3 were those undergone with lateral internal sphincterotomy. Healing rates, pain relief, recurrences, changes in symptoms after the treatment and complications were recorded. Results: There were no statistical difference among groups in terms of age and gender. The healing and symptomatic relief in the sphincterotomy group significantly much more when compared to the other groups (p=0.05). Recurrence rate is very less in sphincterotomy group. Conclusions: Lateral internal sphincterotomy is better treatment option when compared to zinc oxide and lidocaine. There was no difference between zinc oxide and lidocaine treatments.